The effect of magnetic field dependent viscosity on ferromagnetic convection in a rotating sparsely distributed porous medium - revisited - Prakash, J.; Sharma, Kritik R.; Manan, S.; Kumar, P. (Zielona Góra: Uniwersytet Zielonogórski)
The effect of magnetic field dependent (MFD) viscosity on the thermal convection in a ferrofluid layer saturating a sparsely distributed porous medium has been investigated by using the Darcy - Brinkman model in the simultaneous presence of a uniform vertical magnetic field and a uniform vertical rotation.
Keywords: ferrofluid; convection; rotation; magnetic field dependent viscosity; porous medium